Bandwidth‐tunable filtering balun based on compact 3D configuration. Issue 1 (1st January 2019) - Yao, Lidan; Wu, Yongle; Li, Mingxing; Wang, Weimin; Liu, Yuanan
Abstract : For the first time, a novel bandwidth‐tunable filtering balun based on compact 3D configuration is presented. The overall design is basically composed of a two‐layer horizontal feeding plane, a three‐layer vertically mounted plane, and the transmission‐line circuits disposed on both. Implementing the ring resonator in vertical double‐sided parallel‐strip line, the complete horizontal ground and frequency‐independent phase difference are subtly combined. Connecting the shunt varactor diodes with the inserted vertical ground, the desirable filtering property and flexible bandwidth tunability are splendidly fulfilled. A prototype balun centred at 1.53 GHz is fabricated. The measured operating bandwidth is dynamically tuned from 0.87 to 1.23 GHz with a return loss <−10 dB, forcefully validating the design concept.